Modeling the life development quality of regions population - A. A. Golovin (Вестник университета)
Improving the population life quality has been declared a key priority of Russia’s state policy until 2030. The article considers the structure of strategic planning documents for national development goals managment, and also indicates the place of life quality among the main documents. A list of contradictions that hinder effective management of life quality has been identified. Among the contradictions, the author considers the problem of the lack of public databases on the regional population life quality dynamics, the estimation of life quality without monetary meters. The methodological basis of the study was the scientific physical and economic approach to measuring the life quality through complex non-monetary units of measurement, include using the social time budget. The author introduced a new category of “life development quality”, describing the usage features of existing population`s needs and opportunities in time. 16 scenarios for managing the life development quality have been identified. It was carried out modeling of the life development quality of Russian regions population in the period from 2012 to 2020. The regions-leaders and anti-leaders in terms of the life development quality are shown. The object of the study is the life development quality of regions population. The subject of the study is the scenarios for managing the life development quality using non-monetary meters. The purpose of the study is to conduct scenario modeling of the life development quality of regions population.